Respons Publik Muda Islam tentang Kepemimpinan Non-Muslim di Indonesia - Hasse J (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
This paper discusses the young Muslim public's response to non-Muslim leadership in Indonesia. The democratic system provides equal opportunities for everyone to be leaders in various levels of government. However, the debate over non-Muslim leaders remains common, especially in this contemporary era. How the young Muslim public tendency to respond to non-Muslims leadership becomes the point discussed in this paper. This study finds out that there were three young Muslim public tendencies regarding to non-Muslim leadership. First, the tendency of those groups expressively denies the leadership of non-Muslims. The explanation of the Islami texts authority, the Muslim social reality, and the history of national leadership form the basis of this group's thinking. Second, there were groups that accept on the basis of reason, i.e. the social context and political interests, namely anyone has the opportunity and opportunity to be a leader among the Muslim majority. Third, groups that tend to accept with certain conditions, such as having the ability, commitment to uphold the values ​​of Islam, and non-discrimination.